Effectiveness, Leadership Style and Gender of Secondary Education School Principals in Athens, Greece - S, Anastasiou; E, Oikonomou (World Journal of Vocational Education and Training, 2020)
The goal of this work was to investigate the effectiveness of school leaders in relation to gender and leadership style of secondary education principals. A sample (n=163) of secondary education public school teachers in the inner district of Athens, Greece was used. Men outnumbered women in leadership positions in the school district but female principals outnumbered male principals in schools with 200-250 students. Women were underrepresented in school leadership positions in larger schools. The issue of school conflicts varied according to school size; schools with more students had a higher frequency of conflicts than smaller schools. Leadership style did not vary with gender but varied according to the size of the school unit. Principals in small school units (<200 students) more frequently exhibited a laissez-faire leadership style whereas transformational and transactional leadership styles prevailed in larger school units. The frequency of school conflicts varied with the principals’ gender and school size. Male principals were frequently in schools with >250 students. High scores for transformational and transactional leadership traits were inversely correlated with the frequency of school conflict. Transformational and transactional leadership styles were positively correlated to effectiveness, extra effort and satisfaction as outcomes of leadership, whereas a laissez-faire leadership style correlated negatively with these leadership outcomes.